The argumentation in the school sphere: pragma linguistic analysis - Villanueva Chaucas, María Elena (2019)
The present study aims to characterize the school argumentation under the pragma linguistic approach from the analysis of argumentative texts written by a group of adolescents (average age 16) in the last grade of secondary school of regular basic education. Within the framework of this investigation, the pragmatic and linguistic components are explained, such as the illocutionary force of the argumentative act, the rhetorical support and the argumentative orientation. Since the configuration of the school argumentation is shown, the research methodology is designed as a qualitative investigation with descriptive approach. The results show the recurrent use of reservations, declarations of use and reiteration of the point of view in the production of its arguments. On the other hand, the argumentative structure that students design in all their arguments is preferably clustered. Likewise, there was a greater use of co-oriented argumentative connectors, in relation to the anti-oriented ones without neglecting the re-formulators and argumentative operators. As for rhetorical support, the use of argumentative techniques such as pragmatic and definitional arguments is frequent.